Traumatic instability in the knee joint due to an anterior cruciate ligament (ACL) injury in a 23-year-old athlete - Taborska, Nina; Martyka, Anna; Kubicka-Figiel, Martyna (Journal of Education, Health and Sport, 2024)
Introduction In this paper, we aim to present an analysis of the diagnostic, therapeutic, and rehabilitation procedures in a 23-year-old athlete with an anterior cruciate ligament (ACL) injury. The study includes the patient’s medical history, circumstances of the injury, diagnostic and therapeutic procedures applied, as well as the course of postoperative rehabilitation. Objective The objective of our study is to present the anatomy of the ACL, the typical mechanism of injury, and diagnostic and therapeutic possibilities. Methods This is a retrospective study. The medical documentation and imaging studies were subjected to analysis. The analysis was complemented by a literature review based on publications in the English-language PubMed database. Results The case involves a 23-year-old soccer player with an isolated ACL injury in the right knee joint. The case analysis highlights the challenges related to diagnosis and decision-making regarding therapeutic procedures. ACL reconstruction using the STG method and lateral tenodesis with the iliotibial band in combination with postoperative rehabilitation resulted in a positive outcome in terms of knee joint stability and return to sports. Conclusions The review of this medical case underscores the importance of a personalized approach to each patient with an ACL injury, taking into account age, level of physical activity, and coexisting injuries within the knee joint. This allows for the correct decision on the best treatment method for the patient, facilitating a return to sports and minimizing the risk of complications.